Reciprocal priming between receptor tyrosine kinases at recycling endosomes orchestrates cellular signalling outputs - Smith, MP; Ferguson, HR; Ferguson, J; Zindy, E; Kowalczyk, KM; Kedward, T; Bates, C; Parsons, J; Watson, J; Chandler, S; Fullwood, P; Warwood, S; et al. (EMBO Press, 2021)
Integration of signalling downstream of individual receptor tyrosine kinases (RTKs) is crucial to fine‐tune cellular homeostasis during development and in pathological conditions, including breast cancer. However, how signalling integration is regulated and whether the endocytic fate of single receptors controls such signalling integration remains poorly elucidated. Combining quantitative phosphoproteomics and targeted assays, we generated a detailed picture of recycling‐dependent fibroblast growth factor (FGF) signalling in breast cancer cells, with a focus on distinct FGF receptors (FGFRs). We discovered reciprocal priming between FGFRs and epidermal growth factor (EGF) receptor (EGFR) that is coordinated at recycling endosomes. FGFR recycling ligands induce EGFR phosphorylation on threonine 693. This phosphorylation event alters both FGFR and EGFR trafficking and primes FGFR‐mediated proliferation but not cell invasion. In turn, FGFR signalling primes EGF‐mediated outputs via EGFR threonine 693 phosphorylation. This reciprocal priming between distinct families of RTKs from recycling endosomes exemplifies a novel signalling integration hub where recycling endosomes orchestrate cellular behaviour. Therefore, targeting reciprocal priming over individual receptors may improve personalized therapies in breast and other cancers.